The efficacy of paxlovid in elderly patients infected with SARS-CoV-2 omicron variants: Results of a non-randomized clinical trial - Zhong, Weijie; Jiang, Xiufeng; Yang, Xiaosheng; Feng, Tiantong; Duan, Zhixin; Wang, Wei; Sun, Zhaoliang; Chen, Lingyan; Nie, Xin; Zhu, Chuanlong; Zhang, Wenchuan; Li, Yi (Frontiers in Medicine, 2022)
Objective: To evaluate the efficacy of Paxlovid in treating Chinese elder patients infected with SARS-CoV-2 omicron variants. Methods: We performed a non-randomized, controlled trial in Shanghai, China. Participants infected with SARS-CoV-2 omicron variants were enrolled. All patients were divided into the Paxlovid group or the control group according to the Chinese guideline (version 9). The nucleic acid shedding time was the primary endpoint. Results: According to the inclusion criteria, 142 patients infected with omicron variants were enrolled, 36 patients who did not receive paxlovid were assigned to the control group, and 106 were in the Paxlovid group. The baseline characteristics were similar in either group. No significant difference in BMI, age, time from onset to patient enrollment, the severity on first admission, vaccination status, comorbidity, first symptoms, and laboratory results were recorded. Compared to the control group, participants in the Paxlovid group had a shorter viral shedding time [11.11 (2.67) vs. 9.32 (2.78), P=0.001]. Conclusions: In Chinese elder patients infected with the variant of SARS-CoV-2 omicron, our data suggest that Paxlovid can significantly reduce the nucleic acid shedding time.